Dog people: native dog stories - Bruchac, Joseph; Jacob, Murv (Golden, Colo. : Fulcrum Pub., 1995)
A series of stories, set in the northern New England ten thousand years ago, about the special relationship between the Abenaki people and the dogs who were their faithful friends.
Now hear my story -- How the dogs became companions to the people -- The tracks of the giant bear -- Dog people -- Lost in the snow -- The dangerous stranger.
960L
Keywords: Abenaki Indians; Children's stories, American. -- Tales; Abenaki Indians; Indians of North America -- Fiction; Dogs -- Fiction; Short stories